Ecofriendly Management of Major Fungal Foliar diseases affecting yard long bean in Polyhouse - Deepthi S.Nair (Department of Plant Pathology, College of Agriculture, 2019)
The study entitled ‘Ecofriendly management of major fungal foliar diseases affecting yard long bean in polyhouse’ was conducted at College of Agriculture, Vellayani and Integrated Farming System Research Station (IFSRS), Karamana during 2017- 2019 with the objectives to determine the major fungal foliar diseases affecting yard long bean grown in polyhouse; and their management using natural resources and ecofriendly methods. A survey was conducted in 15 polyhouses located at different parts of Thiruvananthapuram district, where yard long bean was cultivated. NS 621 was the most common variety of yard long bean cultivated in polyhouses. Powdery mildew (Disease Incidence (DI) - 100% and Per Cent Disease Index (PDI) - 60.70) and Diaporthe leaf spot (DI - 80% and PDI - 45.77) were the major fungal foliar diseases of the crop observed in these polyhouses. Five varieties of yard long bean viz. Lola, Vellayani Jyothika, Gitika (KAU Varieties), VS 50 (KAU pre release culture) and NS 621 (Namdhari Seeds Private Limited) were screened in the polyhouse at IFSRS, Karamana in completely randomized design (CRD) with four replications, to assess the natural incidence and severity of different fungal foliar diseases. The most susceptible variety to natural incidence of powdery mildew (PDI - 50.89) and Diaporthe leaf spot (PDI - 58.66) diseases was NS 621, whereas VS 50 was tolerant to powdery mildew disease (PDI - 11.11). In vitro evaluation of organic preparations viz, egg-lemon juice extract (10%) and sunflower oil (25 ml) + baking soda (10 g) + bar soap (10 g) + water (5 l), botanicals viz. fermented weed (Setaria barbata) extract (10%) and nimbecidine (0.5%), and non-hazardous compounds viz. potassium silicate (1%) and sodium bicarbonate (0.5%) against Diaporthe tulliensis by poisoned food technique in potato dextrose agar (PDA) medium revealed that fermented extract of S. barbata (10%), sodium bicarbonate (0.5%) and a combination of egg-lemon juice extract (10%) and fermented extract of S. barbata (10%) resulted in cent per cent inhibition of the mycelial growth of the fungus, which were further used for in vivo evaluation. Fermented egg-lemon juice extract (10%), potassium silicate (1%) as well as Psuedomonas fluorescens (KAU isolate) had no inhibitory effect on the mycelial growth of the fungus. A trial was conducted to assess the efficacy of selected treatments for the management of powdery mildew and Diaporthe leaf spot diseases in NS 621 in the polyhouse of IFSRS, Karamana in CRD with eight treatments replicated thrice. The plants sprayed with tebuconazole 50% + trifloxystrobin 25% (WG) (0.04%) (positive control) at 20, 40 and 60 days after planting (DAP) resulted in maximum control of Diaporthe leaf spot (PDI - 4.89) and powdery mildew (PDI - 1.22) diseases. Among the treatments, the combined application of arbuscular mycorrhizal fungi (AMF) (KAU isolate) @ 5g plant-1 at the time of planting along with the foliar application of fermented extract of S. barbata (10%) at 20, 40 and 60 DAP resulted in significant control of Diaporthe leaf spot (PDI - 11.35), whereas the combined application of AMF @ 5g plant-1 at the time of planting along with the foliar application of sodium bicarbonate (0.5%) at 20, 40 and 60 DAP resulted in significant suppression of powdery mildew disease (PDI -11.59). Soil application of AMF alone and foliar application of P. fluorescens (2%) had least effect in reducing the severity of both the diseases. Thus, the present study revealed that powdery mildew and Diaporthe leaf spot were the most important diseases of yard long bean in polyhouses of Thiruvananthapuram district. Soil application of AMF @ 5g plant-1 at the time of planting and foliar spray of fermented extract of S. barbata (10%) or sodium bicarbonate (0.5%) at 20, 40 and 60 DAP were the most effective treatments against Diaporthe leaf spot and powdery mildew diseases respectively, which could be used as a green technology to produce safe-to-eat yard long bean.